Why Thai River Fish Occur Where They are Found - F. William H. Beamish; Punnatut Kangrang; Patchara Nithirojpakdee; Rungthip Plongsesthee (EnvironmentAsia, 2012)
Diversity of freshwater fishes is spatially heterogeneous but, for the most part, the reasons remain poorly understood in Thailand. This review attempts to promulgate factors linking freshwater fishes and habitats, particularly morphological, physiological and ecological, drawing on principles and information from elsewhere but with the focus being Thailand. The review identifies areas in need of improved understanding with an assurance in the future of generous dividends for the investment.